Technological and legislative status point of stationary energy storages in the EU. (March 2019) - Dusonchet, L.; Favuzza, S.; Massaro, F.; Telaretti, E.; Zizzo, G.
Abstract: European renewable generation has been supported through several policy instruments in the last decades, and this has caused a significant growth of the renewable energy sector, spurred by the ambitious climate and energy policy targets. Despite this impetuous growth, the electricity infrastructure is not yet ready to accept increasing shares of variable renewable energy sources (RES) generation, and this is causing grid balance challenges, due to the inherently variable nature of the PV and wind energy. In order to overcome this issue, allowing higher shares of renewable generation in the energy sector, energy storage (ES) systems are becoming increasingly competitive in the global energy landscape, thanks to the positive momentum in research and innovation, making European energy supply more secure, sustainable and affordable. Despite the unarguable benefits, storage technologies still see significant needs for more education among stakeholders, since they are not familiar with technology's benefits and management solutions. In order to fill this gap, this study provides an overview of storage technologies for stationary applications in the EU (plus Bosnia-Erzegovina, Norway and Switzerland), addressing the main trends in European policy legislation, also identifying advantages and barriers for their implementation. Furthermore, based on the analysis of the US Department of Energy (DOE) storage database, the main trends in ES installations within the EU markets are identified, with reference to storage technologies. The analysis carried out in this work could help stakeholders to assess the European storage market evolution in the stationary sector, identifying the main drivers and barriers for each storage technology. Highlights: An overview of ES technologies for stationary applications in the EU is provided. The main trends in European policy legislation are identified. Challenges and barriers related to ES deployment within the EU are outlined. An estimate of ES systems in the stationary sector by country is provided.